Recent Approaches in Magnetic Nanoparticle-Based Biosensors of miRNA Detection - Simge Balaban Hanoglu; Duygu Harmanci; Nursima Ucar; Serap Evran; Suna Timur (Magnetochemistry, 2023)
In recent years, magnetic nanoparticles (MNPs) have been widely used in many fields due to their advantageous properties, such as biocompatibility, easy modifiability, and high chemical stability. One of these areas is the detection of cancer. It is essential to use existing biomarkers, such as microRNAs (miRNAs), for the early diagnosis of this disease. miRNAs are challenging to distinguish and detect in biological samples because they are small, circulating molecules. It is necessary to use more sensitive and feature-rich systems. Thanks to their large surface areas and magnetic moments, MNPs allow easy separation of miRNA at low concentrations from complex samples (urine and blood) and rapid and specific detection in biosensing systems. Here, we discussed the synthesis and characterization methods of MNPs, their stabilization, and MNP-based biosensors in terms of miRNA detection. We considered the challenges and prospects of these biosensor systems in evaluating the development stages, sensitivity, and selectivity.